Multi-response optimization on abrasive water jet machining of Aluminum 7075 alloy using Taguchi-DEAR methodology - Shanmugam, Ayyagounder; Mohanraj, Thangamuthu; Krishnamurthy, Kasilingam; Gur, Ali Kaya; Caligulu, Ugur (Sage Publications Ltd, 2024)
This research aims to conduct the multi-response optimization for abrasive water jet machining (AWJM) of Aluminum 7075 metal matrix composites. The experiments were conducted with three levels of AWJM factors such as pressure, standoff distance, and traverse speed. The experiments were designed using Taguchi's L-9 orthogonal array. The influence of AWJM parameters was assessed by measuring the outcomes like material removal rate, surface roughness, and taper angle. The single response optimization was obtained through Taguchi's signal-to-noise ratio analysis, and multi-response optimization was achieved with Taguchi-data envelopment analysis-based ranking (DEAR). From DEAR, the optimal AWJM parameter 180 MPa of pressure, 3 mm of standoff distance, and 40 mm/min traverse speed was found. After optimization, the surface roughness and taper angle were reduced by 5.44% and 10.92%, respectively. The influence of cutting parameters on the outcomes was examined through the analysis of variance. It was noted that traverse speed had a significant effect and a contribution of 47.79%. After AWJM, the surface was evaluated using SEM analysis, ploughing marks, ductile rupture, and a small crack were observed.
Keywords: Abrasives; surface roughness; taper angle; MRR; Taguchi; DEAR